Evaluation of BNP, uPA and Wint5a in Four Stages of Iraqi Patients with Heart Failure - Raghda Faris Salim; Wafaa Raji Alfatlawi; Muhammed A.H. Aldabagh (AUIQ Complementary Biological System)
Heart disease is classified as one of the most serious and widespread diseases in the world, presenting major challenges to public health and leading to high mortality rates. A comprehensive understanding of its causative factors, along with early recognition of signs and symptoms, is essential to achieve rapid diagnosis and promote preventive measures. This research conducted on 100 Iraqi patients divided into four stages according to the criteria of the American College of Cardiology, where each stage includes 25 patients suffering from heart disease. Their ages ranges (40 -75) years. A comparative analysis was performed with 50 healthy individuals serving as controls. The study used BNP, uPA, and Wnt5a tests, and revealed significantly higher BNP levels among stage IV patients compared to other stages (0.54 ± 0.16, P < 0.001). Wnt5a showed elevated levels in stage III compared to the remaining stages, while uPA did not show statistically significant differences (P value 0.283). In conclusion, measuring BNP and Wnt5a levels is pivotal for accurate diagnosis of heart failure. These biomarkers provide objective evidence of heart dysfunction, helping to differentiate heart failure from other conditions that show similar symptoms.